Get that Fly: Reading 360 Little Books - Mitchelhill, Barbara (Ginn and Company Ltd, 1984)
The New Reading 360 series is designed to provide a solid literary foundation for infants and build on previous literacy knowledge for juniors.
Keywords: Juvenile Fiction-Book